2008
DOI: 10.1097/bot.0b013e31817d97bc
|View full text |Cite
|
Sign up to set email alerts
|

The Biomechanics of Ipsilateral Intertrochanteric and Femoral Shaft Fractures: A Comparison of 5 Fracture Fixation Techniques

Abstract: All constructs showed no statistical differences when compared with one another, with the exception of construct E, which provided the least torsional stiffness. However, the current in vitro model did not simulate fracture healing or support offered by soft tissues, both of which would affect the stiffness and load-to-failure levels reached.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 33 publications
1
47
0
Order By: Relevance
“…Also, a minimum 3-5 Hz loading frequency is required to produce an adequate cyclic surface temperature gradient on the test specimen, which then must be synchronized to the IR camera. Stress maps cannot be generated for one-time events like catastrophic failure of a femur or femur-implant interface [8][9][10][11]13,14,18,19,25,27,[32][33][34][35], since this does not generate a cyclic temperature gradient for synchronization to the IR camera. The high cost of purchase of an IR thermography camera may dissuade some researchers from obtaining one, although some manufacturers of the system may be willing to rent the system.…”
Section: Practical and Clinical Implicationsmentioning
confidence: 98%
See 2 more Smart Citations
“…Also, a minimum 3-5 Hz loading frequency is required to produce an adequate cyclic surface temperature gradient on the test specimen, which then must be synchronized to the IR camera. Stress maps cannot be generated for one-time events like catastrophic failure of a femur or femur-implant interface [8][9][10][11]13,14,18,19,25,27,[32][33][34][35], since this does not generate a cyclic temperature gradient for synchronization to the IR camera. The high cost of purchase of an IR thermography camera may dissuade some researchers from obtaining one, although some manufacturers of the system may be willing to rent the system.…”
Section: Practical and Clinical Implicationsmentioning
confidence: 98%
“…Adduction of femurs is often done in biomechanical studies between 7 • and 25 • [8][9][10][11][12][13][14][15][16][25][26][27]. Proximally, using a 60-mm diameter smooth steel acetabulum-like cup, a vertical (i.e.…”
Section: Strain Gage Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar test regimes and parameters to those currently employed were used in prior studies on synthetic and human femurs. [18][19][20][21][22][23][24][25][26][27][28][29][30][31] All tests were done on a materials testing machine (Model 8874; Instron, Norwood, MA), stiffness was the slope of the force-versus-displacement graph, stiffness results were based on an average of 3 trials, and specimens remained within the linear elastic region to prevent permanent damage before the final axial strength tests, yielding a mean linearity of R 2 = 0.91-0.99.…”
Section: Mechanical Testsmentioning
confidence: 99%
“…Currently, distal anatomical LISS plates are good alternatives in the (9) reported successful results with the combination of LISS plates and proximal femoral nails in the treatment of ipsilateral proximal and distal femoral fractures. Biomechanical studies with combined application of implants for stable fixation of these fractures revealed successful results (10).…”
Section: Case Reportmentioning
confidence: 99%